How does customer advocacy influence brand loyalty? A serial mediation of brand relationship quality and brand trust - Imran Sarmad; Rizwan Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
A variety of psychological and brand-related consequences are connected to customer advocacy. The possible processes behind these correlations are yet not fully understood. The purpose of this study is to investigate the relation that exists between customer advocacy and brand loyalty in the retail banking sector of Pakistan. The brand relationship quality and customer trust act as mediators between customer advocacy and brand loyalty. It is based on a sample of three hundred and fifty consumers from Pakistani retail banks. Partial least squares structural equation modeling was used to analyze the data set and to test the proposed model. The findings provide support to the idea that brand trust and the brand relationship quality may mediate the positive association between consumer advocacy and brand loyalty. These results highlight the importance of brand relationship quality and brand trust in promoting brand loyalty and give some foundational knowledge about how these two factors could interact to boost brand loyalty. This study is the first attempt to investigate the relationship between consumer advocacy and brand loyalty using serial mediation in Pakistani context.
Keywords: 330; Customer advocacy; brand relationship quality; brand trust; cognitive loyalty; affective loyalty; conative loyalty; banking sector